Kode Etik Dalam Meningkatkan Profesionalisme Pendidik, Reaktulisasi dan Pengembangan Kode Etik Guru di Lembaga Pendidikan - Muhammad Maulana Ibrohim; Astuti Darmiyanti; Saprialman Saprialman (Peneliti.net, 2023)
In the teaching profession there is a code of ethics to uphold the dignity of the profession, to protect and maintain the welfare of its members, to increase the dedication of members of the profession, to improve the quality of the profession and to improve the quality of professional organizations. With a code of ethics, teachers are expected to be able to function optimally and professionally, especially in developing the character and ethics of students and upholding the authority of the educational institution and profession. This study aims to describe the application of the school's code of ethics in educational institutions and how the school's code of ethics can improve professionalism in learning. In this study, the authors used a qualitative descriptive research approach and type, with data sources from school principals at the Pamekasan Education Institute, teachers and relevant secondary sources. The results of this study are that the school code of ethics in educational institutions is a way of increasing teacher professionalism so that they comply with the regulations that have been set and agreed upon by the management of educational institutions. The teacher code of ethics which was developed into a school code of ethics is considered an effective method in the process of increasing the professionalism of teachers in this school.